A case report of Klinefelter's syndrome hiding behind pulmonary embolism. Issue 3 (2017) - Xiao, Ping-Xi; Nabeel, Dookhun Muhammad; Zhang, Kai; Yang, Xiao-Hui; Liu, Nian-Nian; Tao, Zhi-Wen; Chen, Xin; Lu, Xin-Zheng
No abstract available